PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS PEGAWAI DINAS PEKERJAAN UMUM PROVINSI KALIMANTAN TIMUR - -, Sudirman - (EKONOMIA, 2014)
The fact that the effective use of labor and directional keys to improving the performance of employees so we need to create a policy that can drive employees to work more productively in accordance with the set. One effort that can be done is to improve the performance of employees, namely by training.Formulation of the problem in this study is whether the training material variables significant effect on employee productivity?; whether the coach variable significantly influence employee productivity ?; whether variables training method significantly influence employee productivity ?; and whether the training variables consisting of training materials, trainers, training methods have significant stimulant effect on employee productivity variable?.Basic theory in this study is focused on the Operations Management Training on Work Productivity. The hypothesis in this study is: "training a significant effect on employee productivity; coach significant effect on employee productivity ?; training methods significantly influence employee productivity ?; and variable training consists of training materials, trainers, training methods have significant simultan effect on the variable employee productivity. "Methods of data analysis in this study is the Multiple Linear Regression Analysis. The results showed that the training variables consisting of training materials (X1), coach (X2) and training method (X3) together (simultaneously) have a significant impact on employee productivity (Y = 1,095 + + 0,214X2 0,300X1 + 0,107X3).Based on the results of the t test, training variables significantly influence employee productivity, coach significant effect on employee productivity, and methods of training a significant effect on employee productivity.Of the three independent variables, the training is a variable that has the greatest influence over the other two variables.